The 'Good Farmer': Farmer Identities and the Control of Exotic Livestock Disease in England. Issue 1 (5th July 2016) - Naylor, Rhiannon; Hamilton‐Webb, Alice; Little, Ruth; Maye, Damian
Abstract: Exotic livestock disease outbreaks have the capacity to significantly impact individual livestock keepers, as well as devastate an entire industry sector. However, there has been limited research undertaken to understand how farmers think about and carry out exotic livestock disease control practices within the social sciences. Drawing on aspects of Social Identity Theory and Self‐Categorisation Theory, this article explores how the 'good farmer' identity concept influences farmers' exotic livestock disease control practices. Using findings from an in‐depth, large‐scale qualitative study with animal keepers and veterinarians, the article identifies three context specific and at times conflicting 'good farmer' identities. Additionally, a defensive component is noted whereby farmers suggest an inability to carry out their role as a 'good farmer' due to government failings, poor practice undertaken by 'bad farmers', as well as the uncontrollable nature of exotic disease.